Implementasi dan Pelatihan Aplikasi Sistem Informasi Penilaian (SIMFONI) Ponpes Nurul Hidayah Cijeruk - Juliasari, Noni; Novita, Ita; Annissa, Jeanie; Mandiri, Tegar (Ikatan Ahli Informatika Indonesia, 2025)
To provide quality education services in line with the 4th goal of the Sustainable Development Goals (SDGs), Islamic boarding schools (pondok pesantren) must adopt measurable and transparent learning mechanisms, particularly in assessment. This Community Service (PkM) activity aims to implement digital-based assessment through the Digital Assessment Information System (SIMFONI) application at Pondok Pesantren Nurul Hidayah Cijeruk. SIMFONI was developed as a technological solution to support an effective, transparent, and accountable assessment process. The application prototype was tested and applied during the PkM activity through six systematic stages: needs analysis and planning, system development, implementation, user training, evaluation and follow-up, and system socialization and maintenance. The results indicate that SIMFONI can be functionally implemented and supports teachers in conducting assessments efficiently, in line with the demands of digitalization in the globalization era.